1977
DOI: 10.1128/aem.34.4.398-402.1977
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four-hour and twenty-four-hour refrigerated storage of nonpotable water for fecal coliform analysis

Abstract: The problem of extending the storage time of water samples for fecal coliform analysis was addressed. Included in this report is a literature review of the storage problem. Twenty-eight samples were analyzed in replicate to determine the effect of 24-h storage of water samples at 40C. A new statistical approach to data analysis, coupled with the concept of practical acceptability, is presented. According to our results, many samples can successfully be stored at 4°C for 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The coliform MPN index is widely accepted, although it is recognized that there are technical, interpretive, and microbiological problems associated with its application (4,6,9,22,23,29,31,41,44,45,51,63,66). Procedures for carrying out the MPN test that have improved selectivity and efficiency have been developed.…”
mentioning
confidence: 99%
“…The coliform MPN index is widely accepted, although it is recognized that there are technical, interpretive, and microbiological problems associated with its application (4,6,9,22,23,29,31,41,44,45,51,63,66). Procedures for carrying out the MPN test that have improved selectivity and efficiency have been developed.…”
mentioning
confidence: 99%
“…Samples were immediately chilled to less than 4'C and tested within 24 h of collection time. Although Standard Methods mandates a maximum 6to 8-h holding time for this type of sample, we chose the 24-h limit since the original A-1 medium work by Andrews and Presnell (2) used a 24-h limit, and Standridge and Lesar (8) showed that carefully iced samples from chlorinated domestic sewage effluents, similar to those used in this study, showed little difference in fecal coliform counts between 8 and 24 h of storage.…”
mentioning
confidence: 99%